Virtual Instrument for Emissions Measurement of Internal Combustion Engines - Armando Pérez; Rogelio Ramos; Gisela Montero; Marcos Coronado; Conrado García; Rubén Pérez (Journal of Analytical Methods in Chemistry)
The gases emissions measurement systems in internal combustion engines are strict and expensive nowadays. For this reason, a virtual instrument was developed to measure the combustion emissions from an internal combustion diesel engine, running with diesel-biodiesel mixtures. This software is called virtual instrument for emissions measurement (VIEM), and it was developed in the platform of LabVIEW 2010® virtual programming. VIEM works with sensors connected to a signal conditioning system, and a data acquisition system is used as interface for a computer in order to measure and monitor in real time the emissions of O2, NO, CO, SO2, and CO2 gases. This paper shows the results of the VIEM programming, the integrated circuits diagrams used for the signal conditioning of sensors, and the sensors characterization of O2, NO, CO, SO2, and CO2. VIEM is a low-cost instrument and is simple and easy to use. Besides, it is scalable, making it flexible and defined by the user.